Algal biodiesel-promising source to power CI engines. (2020) - Dharmaprabhakaran, T.; Karthikeyan, S.; Periyasamy, M.; Mahendran, G.
Abstract: The need of fuel is increasing constantly due to increase in population and industrialization all over the world. The increase in population and industrialization has put the increasing pressure on the use of non-renewable resources. The non-renewable resources like petrol, diesel, coal, natural gas, etc. are used for production of energy. The availability of fossil fuel is continuously decreasing due to increase in demand continuously, these reasons makes the researchers to find new renewable alternative fuel like biofuels. There are various vegetable plants like karanja, neem, soyabean, etc. are used for producting biodiesel only problem is the land availability, so the algae is now been used to produce biodiesel. It has been reported that use of biodiesel reduce the emission and increases the performance of engine. In this review we present an overview about algae use for biodiesel production, including their cultivation, harvesting and processing.